COMPARATIVE EFFECTIVENESS OF DIFFERENT BARIATRIC PROCEDURES ON WEIGHT LOSS AND COMORBIDITIES - FARAZ, A; GUL, A; FAISAL, M (Biological and Clinical Sciences Research Journal, 2024)
Bariatric surgery has revolutionized the treatment of severe obesity, providing not only significant and sustained weight loss but also improvements in obesity-related comorbidities. Objective: The study’s main objective is to compare the effectiveness of different bariatric procedures on weight loss and comorbidities. Methods: This retrospective cohort study was conducted at MTI Lady Reading Hospital Peshawar from 2019 to 2023. Data were collected from 91 patients who wanted weight loss. Participants aged >18 years, with a body mass index (BMI) of 40 or higher or a BMI of 35 or higher accompanied by significant obesity-related comorbidities such as type 2 diabetes, hypertension, or obstructive sleep apnea, were included in the study. All included patients underwent one of the four bariatric procedures. Results: The study included 91 patients who underwent various bariatric procedures at MTI Lady Reading Hospital between 2019 and 2023. The mean age of participants was 42.38 ± 2.35 years. The gender distribution comprised 55 females (60%) and 36 males (40%). The patients’ mean preoperative body mass index (BMI) was 45.2 ± 3.01 kg/m². Biliopancreatic diversion with duodenal switch (BPD/DS) demonstrated the highest effectiveness, with an average %EWL of 78% at three years and the highest resolution rates for type 2 diabetes (95%), hypertension (90%), and obstructive sleep apnea (85%). Roux-en-Y gastric bypass (RYGB) also showed substantial weight loss and comorbidity resolution, achieving an average %EWL of 68% at three years. Conclusion: It is concluded that bariatric surgery is a highly effective intervention for achieving significant weight loss and resolving obesity-related comorbidities. Among the procedures studied, biliopancreatic diversion with duodenal switch (BPD/DS) demonstrated the highest effectiveness, with substantial weight loss and resolution rates for type 2 diabetes, hypertension, and obstructive sleep apnea.